Comparative study of ormeloxifene and low dose oral contraceptive pill for the treatment of dysfunctional uterine bleeding in peri-menopausal age group - Shah, Maitri; Parmar, Chirayu; Gor, Riddhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Dysfunctional uterine bleeding (DUB) is the most common menstrual disorder of women in any age group and is a diagnosis of exclusion. Medical management of menorrhagia is a difficult task as there are wide variations in the available drugs and a lot of different regimes are available. Present study evaluates efficacy and safety of ormeloxifene a selective estrogen receptor modulator (SERMs) as compared to combined oral contraceptive pills in treatment of dysfunctional uterine bleeding in perimenopausal women. Methods: Total 60 patients meeting with our inclusion and exclusion criteria were enrolled in the study over a time period of 6 months and were further divided randomly into two groups. One group was given Ormeloxifene and the other group was treated with combined oral contraceptive pills (COCP) over a period of six months. The outcome variables noted were pictorial blood loss assessment chart (PBAC) score, Hb level and combined endometrial thickness (CET). Quantitative variables were compared using independent t test/Mann-Whitney test between the two groups and paired t Test/Wilcoxon test was used for comparison between pre and post within the group. Results: Both ormeloxifene and COCP significantly reduce blood loss in these patients evidenced by decrease of PBAC score, rise in hemoglobin levels and decrease in CET levels. However, ormeloxifene was found to be superior to COCP in reducing the menstrual blood loss. Ormeloxifene was also tolerated better compared to COCP with fewer side effects experienced by patients.